2021
DOI: 10.1109/access.2021.3067818
|View full text |Cite
|
Sign up to set email alerts
|

A Nonlinear Tire Blowout Stabilizer Based on a Novel Integral Terminal Sliding Mode Controller

Abstract: This paper proposes an automatic corrective safety controller design and evaluation based on braking/traction actuation to enhance the stability of a ground vehicle subjected to a tire blowout. Along with the nonlinear Dugoff's tire model, a nonlinear planar seven degrees of freedom control-oriented vehicle model is developed and validated using MSC Adams/ car package. The proposed novel controloriented model accounts for the longitudinal dynamics, large steering and slip angles, and the nonlinearities associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…By cutting the burst parts of the tire, it was found that cracks mainly initiates at the end of the tire belt layer. [25][26][27] The tire will be greatly impacted in a short time, which will cause the belt layer to break, and consequently cause the whole tire to burst. The end of the belt layer is the joint part of steel cord and rubber material, which is easy to form cracks.…”
Section: Tire Structure Analysismentioning
confidence: 99%
“…By cutting the burst parts of the tire, it was found that cracks mainly initiates at the end of the tire belt layer. [25][26][27] The tire will be greatly impacted in a short time, which will cause the belt layer to break, and consequently cause the whole tire to burst. The end of the belt layer is the joint part of steel cord and rubber material, which is easy to form cracks.…”
Section: Tire Structure Analysismentioning
confidence: 99%